SAMBUNGAN BALOK BETON BERTULANG PRACETAK DENGAN LAPISAN CFRP DAN PLAT BAJA - Da ConceiÃ§Ã£o, Gilberto De Carvalho; Lisantono, Ade (Jurnal Teknik Sipil, 2019)
Precast reinforced concrete beams are building structures without using on-site casting and can shorten construction time and reduce costs and labor. In this research a method was used to overcome the shortcomings of the precast method in terms of weight and size, by dividing the precast segment into a new connection between the beam to the beam where the connection was reinforced with Carbon Fiber Reinforced Concrete (CFRP) and Steel Plate. Where there are 2 beam joints namely Type II connection on the connection area, steel plate and bolt data are used as Type III washers and joints, CFRP is added to the joint area and 6 mm thick steel plate and 20 mm diameter bolt. The dimensions of the beams used are 150 x 250 x 3200 mm with 4P10 longitudinal reinforcement as pressure reinforcement and 2P10 as pressure reinforcement. While 2P8-200 as shear reinforcement in the field area, 2P8-150 for connection area and 2P8-100 for support area. Where the quality of reinforcing steel in this method is BjTP 24, with a yield stress of 323.533 MPa for P10 and 237,249 MPa for P8. According to the results of the study the beam joints with centralized loading, the type II joint beam obtained a load capacity of 2782,718 kg while the type III connection experienced a load increase of 3553,875 kg due to the addition of CFRP layers on the beam joints.